On the mechanical characteristics and parametric optimisation of friction stir welded magnesium AZ31B alloy. (2019) - Gulati, Piyush; Shukla, Dinesh Kumar
Friction stir welding (FSW) is an effective joining technique to produce sound defect free welds. The various process and tool parameters play significant roles in producing sound welds and deciding the joint characteristics. In the present research work, the tensile strength (TS) and impact energy (IE) of friction stir butt-welded AZ31B magnesium alloy were investigated. The empirical relationships between the FSW input process parameters (tool rotational speed, tool welding speed, and plunge depth) and the output responses (tensile strength and impact energy) were established. The welding conditions to maximise the tensile strength and impact energy were optimised and reported. The microstructure of the friction stir welded joints were investigated using optical microscopy and the grain size was also determined. Rotational speed was found as the most significant parameter for maximising the tensile strength and impact energy. Further, the friction stirring of the selected base metal has affected the grain structure of the processed metal and an average reduction of 6 μm in grain size was observed microscopically.